(untitled) (International Journal of Food and Nutritional Sciences, 2022)
India tops in utilization of social networking sites and monetary establishments are digitalizing the exchanges quickly. Bitcoin is an electronic financial system providing similar features as our current financial system. RBI has taken measures to direct Bitcoins. RBI cautions Indians about the danger implied in exchanging cryptographic money. The absence of information about the working of cryptographic money exchanges, it has let to fraudulent exchanges and losing the speculation made in something very similar. Bitcoin as an asset, it has had perhaps the most unpredictable trading history. Kanyakumari district has a large population of small investors belonging to middle class household. The perception of the investors are influenced by unstable return, insecurity of investment, lack of regulators and market volatility. Bitcoin is a highly volatile and prices can increase and decrease by very huge amount in just fraction of minutes or even just seconds. Though it gives highest return but once it hits the bottom, investors can lose all they have in it. The paper highlights the views of investors based on different factors. This article based on primary data through structured questionnaire. The result of the study provides new insights into the investors in cryptocurrencies.